2006
DOI: 10.1002/bmc.684
|View full text |Cite
|
Sign up to set email alerts
|

Determination of active constituents inLonicera confusa DC. by capillary electrophoresis with amperometric detection

Abstract: A method based on capillary electrophoresis with amperometric detection has been developed for the determination of luteolin, chlorogenic acid, 3,5-dicaffeoylquinic acid and caffeic acid in the dried flower buds, leaves and stems (three medicinal parts) of Lonicera confusa DC., respectively. The effects of several important factors such as detection potential, the concentration of the running buffer, separation voltage and injection time were investigated to acquire the optimum conditions. The detection electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The CE-ECD system used has been described previously (Chen et al, 2006a,b;Yao, 2006). A ±30 kV high-voltage dc power supply (Shanghai Institute of Nuclear Research, China) provided a separation voltage between the two ends of the capillary.…”
Section: Methodsmentioning
confidence: 99%
“…The CE-ECD system used has been described previously (Chen et al, 2006a,b;Yao, 2006). A ±30 kV high-voltage dc power supply (Shanghai Institute of Nuclear Research, China) provided a separation voltage between the two ends of the capillary.…”
Section: Methodsmentioning
confidence: 99%
“…The result was in agreement with the previous reports (Xiang et al, 2001;Makoto et al, 2002), which showed that the caffeoyl was the active group of caffeoylquinic acid derivatives and it could increase the activity of this type of compounds. In addition, the other bound compounds such as caffeic acid, rutin, quercetin-3-O-glucoside, luteolin-3-O-glucoside, lonicerin, isomer chlorogenic acid and isomer of di-O-caffeoyl quinic acid were all proven bioactive compounds, which had been used as quality control markers of FLJ (Yao et al, 2006;Ma et al, 2005;Huang et al, 2005). Therefore, it is believed that this proposed analytical method could be applied in screening bioactive compounds in TCMs.…”
Section: Identification Of Components In Fljmentioning
confidence: 97%
“…Chen's group separated and determined clenbuterol, cimaterol, and salbutamol in feed and urine [73], perphenazine and fluphenazine in tablet, spiked urine, and rabbit serum samples [74], and L-tyrosine and its metabolites in rabbit's urine [75]. Yao et al [76] monitored bioactive constituents (luteolin, chlorogenic acid, 3,5-dicaffeoylquinic acid, and caffeic acid) in real plant samples. CE -AD can also serve as an analysis tool to detect active ingredients in drug [77 -79], Chinese herbal medicines [80], and isomers [81 -83].…”
Section: Introductionmentioning
confidence: 99%